(Aloe vera as a raw Material for Industry) - Wahyu Suryowidodo, C (Warta Industri Hasil Pertanian, 1988)
Aloe vera is a kind of succulent plant. It is a member of the Lily family and can be used as a raw material for industries. This article described the components of the aloe gel, its physical and chemical properties, the use of the gel for human health, cosmetic, food and beverage industries.